2011
DOI: 10.1073/pnas.1014033108
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the paternal genome upon fertilization involves genome-wide oxidation of 5-methylcytosine

Abstract: Genome-wide erasure of DNA cytosine-5 methylation has been reported to occur along the paternal pronucleus in fertilized oocytes in an apparently replication-independent manner, but the mechanism of this reprogramming process has remained enigmatic. Recently, considerable amounts of 5-hydroxymethylcytosine (5hmC), most likely derived from enzymatic oxidation of 5-methylcytosine (5mC) by TET proteins, have been detected in certain mammalian tissues. 5hmC has been proposed as a potential intermediate in active D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
494
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(548 citation statements)
references
References 47 publications
(80 reference statements)
40
494
2
10
Order By: Relevance
“…Furthermore, a study of the DNA methylation pattern in human 3PN zygotes established that active demethylation of the paternal PN occurs post-fertilization in both c-IVF and ICSI [32]. In addition, recent studies have shown that the demethylation of paternal PN is induced by conversion from 5mC to 5hmC by ten-eleven translocation methylcytosine dioxygenases (TETs) [9][10][11]. Among TET proteins, TET3 is intensely expressed in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study of the DNA methylation pattern in human 3PN zygotes established that active demethylation of the paternal PN occurs post-fertilization in both c-IVF and ICSI [32]. In addition, recent studies have shown that the demethylation of paternal PN is induced by conversion from 5mC to 5hmC by ten-eleven translocation methylcytosine dioxygenases (TETs) [9][10][11]. Among TET proteins, TET3 is intensely expressed in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that 5-methylcytosine (5mC) in the paternal genome is specifically converted to 5-hydroxymethylcytosine (5hmC) during the pronuclear stage [9][10][11]. Although these three studies were conducted in animals, we applied a similar approach in this study, using epigenetic divergence to determine the origin of mPN and fPN in abnormal human zygotes with 1PN and 3PN.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Further biological studies and genome-wide profiling of 5hmC have revealed significant roles played by this modified base in stem cell differentiation, leukemia, epigenetic reprogramming, neurodegenerative diseases, hypoxia, and angiogenesis. [7][8][9][10][11][12][13][14][15] These findings have fostered wide speculation that 5hmC modification is an important epigenetic modification after 5mC. [16] In collaboration with two groups, we contributed to the discovery that 5hmC could be further oxidized to 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) (Figure 1).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Tet1 maintains the stem cell properties of embryonic stem cells, [6,8] Tet2 significantly affects leukemia, [9][10][11][12][13] and Tet3 plays a key role in epigenetic reprogramming in zygote development. [14,15] Here we present that the active domain of the mouse Tet1 can not only oxidize 5mC in duplex DNA, but also 5mC in single-stranded DNA (ssDNA), indicating that Tet proteins can potentially be involved in DNA replication or/and transcription, as well as directly oxidizing the corresponding modifications on RNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the demethylation pattern is different in each parental chromatin, while maternal genome is slowly and passive, the paternal is fast and active (MAYER et al, 2000;OSWALD et al, 2000). For a long time the active process was unknown, however in 2011 studies showed that the responsibility for such process is the formation of 5-hydroxymethylcytosine (5-hmc), a cytosine variation, in which a -OH is added to the methylated cytosine by a protein from the Tet family; Tet 1, 2 or 3 (IQBAL et al, 2011;WOSSIDLO et al, 2011). Tet 1 and 2 have been related to embryonic stem cells pluripotency and depletion of Tet1 implicates in lineage differentiation difficulties (COSTA et al, 2013).…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 99%